Modeling of logistics flows in the construction of low-rise buildings from prefabricated structures - Osipov, Oleksandr; Yemelianova, Olena (Ways to Improve Construction Efficiency, 2025)
The article investigates the urgent problem of optimizing logistics flows during the construction of low-rise residential buildings using prefabricated and modular structures. Given the current economic and geopolitical instability in Ukraine, particularly the need for the rapid restoration of the housing stock for internally displaced persons, the low-rise construction sector is experiencing unprecedented development. Traditional methods of organizing construction projects are often characterized by insufficient coordination among participants, inefficient resource management, and high costs, which is unacceptable under limited funding and tight deadlines. The purpose of the study is to develop and justify comprehensive logistics models based on the principles of integrating modern enterprise resource planning (ERP) systems and building information modeling (BIM). The paper analyzes the conceptual foundations of the intellectual analysis of transport and logistics systems, allowing for the rational choice of counterparties, optimization of delivery routes, and control of inventory levels. Significant attention is paid to the implementation of innovative IT solutions, such as Supply Chain Management (SCM), Transport Management Systems (TMS), and Warehouse Management Systems (WMS), which together provide a 15–20% reduction in logistics costs. Based on a solid mathematical framework, the article proposes functions for calculating the integral efficiency of digital management, the level of resource synchronization between ERP and BIM, and scenario smoothing for material resource buffers. It is proven that the application of "Just-in-Time" (JIT) concepts and Material Requirements Planning (MRP) systems makes it possible to minimize downtime, reduce environmental impact, and introduce "green logistics" principles. The main barriers to the digital transformation of construction logistics are identified, and recommendations for overcoming them, including the use of SaaS solutions and personnel training, are developed. The practical value of the results lies in creating a reliable methodological toolkit for construction and development companies aimed at increasing profitability, reducing the duration of low-rise housing construction, and ensuring the sustainable development of the national economy in post-war reconstruction.